Sitnik OFM: Wspomnienia Bernardynki łowickiej Weroniki Kempy z okresu II wojny światowej - Sitnik, Aleksander K. (Archiwa, Biblioteki i Muzea Kościelne, 2014)
During World War II, the Bernardine Sisters from Łowicz were involved in intense charitable activities. In the September campaign during the Battle of Bzura, the Bernardine Sisters Convent was transformed into a hospital. Sisters organized beds for patients, underwear, bedding and food. They helped Polish offi cers imprisoned in Blich (the district of Łowicz) and those who waited for the deportation to Germany. They also provided assistance to the Jews from the ghetto of Łowicz. In 1944 they freed 150 children exported from Warsaw to Germany after the Warsaw Uprising and took them to the convent. There, they organized an orphanage for children who lost parents in the war. The person who was especially involved in that kind of activity was Weronika Kempa, the author of the memoirs of that time.